Quantitative statistical evaluation of maxillary and mandibular incisor root canal morphology in Saudi patients - Yousef Aldahman; Peter M. B. Cahusac; Saad Alnazhan; Ayman Mandorah; Ra'ed Alsadhan; Asma Aljebaly; Faisal Alnassar; Abdulrahman Alolayan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Clinical practice demands understanding the complexity of the root canal system to achieve desired treatment goals. The statistically detailed morphology of the tooth and root canal morphology is very important to know. Therefore, the present study aims to investigate the statistical analysis of root canal morphology and morphological variations of maxillary and mandibular incisor teeth using cone-beam computed tomography (CBCT) in Saudi patients attending King Saud University Dental Hospital. Materials and Methods: CBCT images of 480 patients were selected. Number of roots and root canal configuration were identified and categorized according to Vertucci's classification. Tooth length, distance from cementoenamel junction (CEJ) to the area of canal division, and width of the canal at the area of division were also evaluated. Bilateral symmetry and association between gender and age with the different variables were investigated. Data were analyzed using Chi-square, multiple linear regression, and McNemar's tests. Results: A total of 3412 teeth were evaluated. All maxillary teeth had one root with Type I canal configuration. For mandibular teeth, all exhibited one root with the majority having Type I canal configuration in central (71.2%) and lateral (75%) incisor teeth. There was a statistically significant association between number of canals and age in mandibular incisor teeth observed only in females (P < 0.001), while no association was observed between canal configuration and gender (P = 0.900 and P = 0.721, respectively). Multiple regression analyses showed that age and gender significantly explain the difference of the variance in tooth length (P < 0.001). Moreover, bilateral symmetry was observed in 98.1% of mandibular central and 97.6% of lateral incisor teeth with no statistically significant association (P = 1 and P = 0.058, respectively). Conclusion: All maxillary and most mandibular incisor teeth present with one root and Type I canal configuration. In general, males have longer teeth than females, with a significant decrease in length with each year increase in age. Mandibular lateral incisor teeth exhibited the highest mean distance from CEJ to point of canal separation and highest mean width in the area of canal division.